Predicting Injury Risk in Sports Students: A Gender-Based Review - Cahulul Rizaldy Hasan; Khoiril Anam (Universitas Pendidikan Indonesia, 2024)
Anyone, even sports students, can experience sports injuries. The risk of injury experienced by students is even greater if a basic understanding of exercise does not accompany it; warming up and cooling down have an essential role in reducing risk. This study aims to determine the risk of injury to new students of the Sports Science Study Program class 2023. The research method uses a quantitative research design. The method used in the study was a survey method with tests and measurements. The sample withdrawal technique uses a total sampling technique. The sample used amounted to 119 students. Data analysis refers to the Functional Movement Screen score, which has 7 test movements. The results showed that female data were 33 samples, 67% of students had a low risk of injury, and 33% were in the medium injury risk category. No students were in the high-injury risk category. In comparison, male data were 86 samples: 6% of students were in the high injury risk category, 46% were in the medium injury risk category, and 48% were in the low injury risk category. The findings of the results in this study are that some samples have good fundamental movement patterns seen from the FMS scoring that has been done. The limitation of this study is that the samples used are students from various sports with various sports. Future research should be conducted prospectively, which includes a detailed injury survey on each individual and a more precise definition of injury to determine the physical condition of the sample before conducting the test.